Portable Electric Hoist for Effectiveness of Construction of 3rd Floor Houses - Arnol, M Yusuf; Febriyati, Nur Ahlina (Transactions on Engineering and Computing Sciences, 2019)
The development of a city can be measured by the amount of development that has been carried out and its suitability for people needs, which is seen by the increase of demand for Building Construction Permits (IMB certificate) because around 70% of regional income is derived from levies in this sector. The population density of a residential area is no longer possible developed by horizontally, along with the increase in the needs of dwellings and businesses to meet the needs of the construction of houses and businesses by building them in 3rd floor houses Lifting equipment type portable electric hoist is a tool which used to move material from the first floor to the next floor during the construction of 3rd floor houses. The transferred material includes; bricks, ceramics, cement, and other building materials. This research conducted to analyze the design of a Lifting Equipment for Material type portable electric hoist to increase the effectiveness of the construction of 3rd floor houses. This study uses a direct load testing method by lifting up to the maximum test load or tipping load. Lifting and moving of test loads is determined at an altitude of 5 meters and 12 meters from the ground floor surface The results of this research indicates that the five stages load carried out by lifting and moving materials test loads by the design of a portable electric hoist were accepted. Lifting and moving load at sixth floor is rejected because condition of tipping. The rejection of the results from this test became a reference to determine the maximum safe working load for operational design of portable electric hoist only 300 kilograms